The Relationship between Financial Development and Economic Growth in Qatar - AL-KHULAIFI, Abdulla S (Asian Journal of Empirical Research, 2013)
The relationship between financial development and economic growth has attracted a great deal of attention among economists and policy makers alike. The economy of Qatar did not receive much attention in the empirical literature. This study attempts at filling this gap in economic literature, and examines the causal relationship between financial development and economic growth in Qatar for the period 1980-2012. Annual data were used, and the unit root properties of the data set are tested using Augmented Dickey-Fuller (ADF) test. Variables were found to be stationary at first difference. This was followed by Johansen cointegration technique to test the long-run relationship between variables. Three proxies for financial development were specified. Those were the ratio of broad money (M2) to Gross Domestic Product (GDP), the ratio of total bank deposits to GDP and the ratio of total credit to private sector to GDP. Economic growth was found to be cointegrated with the three proxies for financial development. Granger causality test was performed, and results suggest that causality runs from economic growth to financial development in Qatar.